Cardiopulmonary exercise testing and efficacy of percutaneous coronary intervention: a substudy of the ORBITA trial - Ganesananthan, Sashiananthan; Rajkumar, Christopher A; Foley, Michael; Thompson, David; Nowbar, Alexandra N; Seligman, Henry; Petraco, Ricardo; Sen, Sayan; Nijjer, Sukhjinder; Thom, Simon A; Wensel, Roland; Davies, John; et al. (European heart journal, 2022)
Abstract Aims Oxygen-pulse morphology and gas exchange analysis measured during cardiopulmonary exercise testing (CPET) has been associated with myocardial ischaemia. The aim of this analysis was to examine the relationship between CPET parameters, myocardial ischaemia and anginal symptoms in patients with chronic coronary syndrome and to determine the ability of these parameters to predict the placebo-controlled response to percutaneous coronary intervention (PCI). Methods and results Patients with severe single-vessel coronary artery disease (CAD) were randomized 1:1 to PCI or placebo in the ORBITA trial. Subjects underwent pre-randomization treadmill CPET, dobutamine stress echocardiography (DSE) and symptom assessment. These assessments were repeated at the end of a 6-week blinded follow-up period. A total of 195 patients with CPET data were randomized (102 PCI, 93 placebo). Patients in whom an oxygen-pulse plateau was observed during CPET had higher (more ischaemic) DSE score [+0.82 segments; 95% confidence interval (CI): 0.40 to 1.25, P = 0.0068] and lower fractional flow reserve (−0.07; 95% CI: −0.12 to −0.02, P = 0.011) compared with those without. At lower (more abnormal) oxygen-pulse slopes, there was a larger improvement of the placebo-controlled effect of PCI on DSE score [oxygen-pulse plateau presence (Pinteraction = 0.026) and oxygen-pulse gradient (Pinteraction = 0.023)] and Seattle angina physical-limitation score [oxygen-pulse plateau presence (Pinteraction = 0.037)]. Impaired peak VO2, VE/VCO2 slope, peak oxygen-pulse, and oxygen uptake efficacy slope was significantly associated with higher symptom burden but did not relate to severity of ischaemia or predict response to PCI. Conclusion Although selected CPET parameters relate to severity of angina symptoms and quality of life, only an oxygen-pulse plateau detects the severity of myocardial ischaemia and predicts the placebo-controlled efficacy of PCI in patients with single-vessel CAD. Structured Graphical Abstract Structured Graphical Abstract Only an oxygen pulse plateau relates to markers of ischaemia and predicts the placebo-controlled efficacy of percutaneous coronary intervention in patients with chronic coronary syndrome.